2020
DOI: 10.1007/s40955-020-00162-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered perspective on the barriers to learning participation of disadvantaged adults

Abstract: We propose a multi-level explanatory model aimed at explaining the variability behind participation in adult learning. Our model focuses on the employed adults, narrowing down to vulnerable subgroups of employed: low-skilled; young and low-skilled, and immigrants. Adult learning participation is explained identifying determinants at the level of the individual, household, job, employer as well as the system-level. The model is estimated using the European Union Labour Force Survey microdata for 28 European cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…For education level, we can corroborate an increasing significance of participation inequality in nonformal adult education based on the highest education attainment. This confirms results from previous studies (Boeren, 2016, 2017; Cabus et al, 2020; Cincinnato et al, 2016). In our data, this micro‐social factor of adult involvement in organised learning has become more significant in the recent two decades (Kalenda et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For education level, we can corroborate an increasing significance of participation inequality in nonformal adult education based on the highest education attainment. This confirms results from previous studies (Boeren, 2016, 2017; Cabus et al, 2020; Cincinnato et al, 2016). In our data, this micro‐social factor of adult involvement in organised learning has become more significant in the recent two decades (Kalenda et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The data from the analysis can help institutions formulate effective education policy and practices for dealing with the adverse outcomes of the pandemic. In the context of international comparative research (e.g., Cabus et al, 2020;Cincinnato et al, 2016;Dämmrich et al, 2014;Lee & Desjardins, 2019), our results show the impact of the first wave of pandemic on the adult education system in one of the most negatively affected European countries in terms of the participation in nonformal adult education as well as how responses to the pandemic reinforced the inequality already existing in the system.…”
Section: Pattern Of Perceived Barriers To Involvement Among Nonpartic...mentioning
confidence: 73%
“…The latter is also achieved by collaborative programing and delivery (Martin & Muders, 2018). Regional institutional and policy frameworks can affect participation, especially of disadvantaged, low-educated groups (Cabus et al, 2020).…”
Section: International Research On the Regulation And Provision Of Ad...mentioning
confidence: 99%
“…Institutional barriers include institutional practices and procedures that discourage or prevent participation. Research has shown that there are country specific institutional arrangements that determine the levels of barriers and enable individuals to overcome them (Cabus et al, 2020; Hovdhaugen & Opheim, 2018; Roosmaa & Saar, 2016).…”
Section: Participation In Aet and Risk Of Job Automationmentioning
confidence: 99%